2021
DOI: 10.1140/epjp/s13360-021-01239-9
|View full text |Cite
|
Sign up to set email alerts
|

New estimate of the chromomagnetic dipole moment of quarks in the standard model

Abstract: A new estimate of the one loop contributions of the standard model to the chromomagnetic dipole moment (CMDM) μq of quarks is presented with the aim to address a few disagreements arising in previous calculations. We consider the most general case with non-zero gluon transfer momentum q 2 and obtain analytical results in terms of Feynman parameter integrals and Passarino-Veltman scalar functions, which are then expressed in terms of closed form functions when possible. It is found that the QCD contribution fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 47 publications
(57 reference statements)
1
17
0
Order By: Relevance
“…Regarding to the top quark CMDM, the experimental CMS Collaboration reported that μExp t = −0.024 +0.013 −0.009 (stat) +0.016 −0.011 (syst) [6], at 95% C. L., using proton-proton collisions at the centre-of-mass energy of 13 TeV with an integrated luminosity of 35.9 fb −1 . Within the SM context, the CMDM has been exhaustively studied from the three-body g tt coupling [1][2][3][4], at the one-loop level, where the most promising prediction establishes that Re μt (−m 2 Z ) = −0.0224 [2,3], which supports the solidity of the model. This last result was computed in the spacelike domain (s = −m 2 Z ), just as α s (m 2 Z ) is conventionally evaluated for high-energy physics [7][8][9][10][11], where the energy scale is fixed at the mass of the Z boson.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Regarding to the top quark CMDM, the experimental CMS Collaboration reported that μExp t = −0.024 +0.013 −0.009 (stat) +0.016 −0.011 (syst) [6], at 95% C. L., using proton-proton collisions at the centre-of-mass energy of 13 TeV with an integrated luminosity of 35.9 fb −1 . Within the SM context, the CMDM has been exhaustively studied from the three-body g tt coupling [1][2][3][4], at the one-loop level, where the most promising prediction establishes that Re μt (−m 2 Z ) = −0.0224 [2,3], which supports the solidity of the model. This last result was computed in the spacelike domain (s = −m 2 Z ), just as α s (m 2 Z ) is conventionally evaluated for high-energy physics [7][8][9][10][11], where the energy scale is fixed at the mass of the Z boson.…”
Section: Introductionmentioning
confidence: 84%
“…In the Standard Model (SM), the anomalous chromomagnetic dipole moment (CMDM) is induced at the oneloop level and receives contributions from quantum chromodynamics (QCD), electroweak (EW) and Yukawa (YK) sectors [1][2][3][4]. Moreover, it has already been established in the literature that the non-static CMDM (μ t (q 2 )) is consistent with the properties of an observable, since this one is gauge invariant, gauge independent, infrared (IR) finite and ultraviolet (UV) finite [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Off-shell couplings have been of great interest in recent years [35][36][37] as they can develop an imaginary (absorptive) part due to the optical theorem, thereby giving rise to some effects on physical processes. Such a property has been studied for instance in the off-shell chromomagnetic and chromoeletric dipole moments of quarks [38,39], where the gluon is off-shell, and also in the trilinear neutral gauge boson couplings [40,41], which are non-vanishing when at least one of the three gauge bosons is off-shell [42,43]. Also, the phenomenological implications of the absorptive part of the off-shell Higgs boson couplings have been brought to attention by many authors [18,20,22,28], nonetheless, to our knowledge, a precise determination of the SM contribution has not been reported yet, which may stem from the fact that there has been some controversy on whether or not off-shell couplings represent valid observable quantities.…”
Section: Introductionmentioning
confidence: 99%
“…From the theoretical point of view, it is known that the CMDM of the SM quarks cannot be well defined in a static scenario, that is to say, when q 2 = 0; it can only be established an off-shell CMDM, which is consistent with an observable given that it is gauge invariant, gauge independent, infrared finite and ultraviolet finite [11,12,26,27]. Thus, we will present the evaluation of this observable considering an off-shell gluon (q 2 = 0) at large-momentum transfer.…”
Section: Introductionmentioning
confidence: 99%